An empirical analysis on the impact of online community engagement on the purchase intention of generation Z customers : a focus on luxury skincare brands - Marchesan, Sofia (2024)
This dissertation examines the dynamic intersection of social commerce, online communities, and luxury skincare products. Luxury skincare companies are using online communities more and more to increase customer engagement and boost sales as a result of the growth of digital platforms. In order to investigate this phenomenon, the research uses a mixed-method approach to examine how social commerce strategies affect young consumers' behavior and purchase intention in the luxury skincare market. It does this by thoroughly reviewing the body of extisting literature, and integrating both qualitative and quantitative analyses. To gather qualitative insights, individual interviews were conducted, focusing on consumers' interactions with brands through social media platforms and online communities. Moreover, a questionnaire was distributed among Generation Z consumers living in Italy and the data derived from this survey was rigorously analyzed to uncover patterns and correlations. Through this methodology, the research gathered key insights into how online communities are perceived and allow consumers to interact, particularly in the context of luxury skincare. The discussion section delves into the implications of these findings, emphasizing the role of digital engagement in shaping consumer preferences. As a result, the conclusion of this thesis highlights the critical role that online communities play, offering strategic insights for luxury skincare brands aiming to leverage these platforms for customer engagement and market growth. It points out the role of interaction by revealing that community-driven marketing influences consumer purchasing decisions, contributing to the academic understanding of online communities and providing practical recommendations for the luxury skincare industry.